Southeast Asia Report - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1986)
This report contains translations/transcriptions of articles and/or broadcasts on Southeast Asian countries. Titles include: Official Discusses Danger of 'Militant Sects'; Wellington Envoy on Antarctic Talks, Developments; Groups Object to Solarz Visit to Research Center; French Firm Advising on Design for Satellites; Further Reportage on Mongolian Friendship Hospital; Marcos Frees Detained Priest; Officials Urge Foreclosed Land to Displaced Workers; Leyte Farmers Request Human Rights Investigation; Prince (Thailand) Warns Troops on Illegal Activities; Editorial Questions Sihanouk Sincerety; and others.